The Masters of Truth in the Middle-Earth or the Worlds of Fantasy as Seen through the Lens of Detienne’s Theory - Komorowska, Joanna (Załącznik Kulturoznawczy, 2018)
The essay analyzes the importance of true speech (as described in M. Detienne’s Les Maîtres de Vérité) in epic fantasy. Starting with J.R.R. Tolkien’s Middle-Earth, through Lyndon Hardy’s magical worlds, Ursula LeGuin’s Earthsea and AnnMcCaffrey’s Dragonriders of Pern series, speech carries an added value of truth, preserving and shaping the universe in turn – such understanding of privileged speech links modern fantasy literature to its ancient models (Homer or Hesiod).